Effect of Various Dual-Phase Heat Treatments on the Corrosion Behavior of Reinforcing Steel Used in the Reinforced Concrete Structures - Keleştemur, Oğuzhan; Yıldız, Servet (My University, 2009)
In this study, corrosion behavior of six different dual-phase (DP) steels with varying morphologies and martensite content has been examined in comparison to ferrite–pearlite steel in concrete. Intercritical annealing and intermediate quenching heat treatments have been applied to the reinforcing steel in order to obtain DP steels with different morphologies and content of martensite. Corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of steels embedded in concrete was measured every day for a period of 30 days in accordance with ASTM C 876 standard. In the second stage, anodic and cathodic polarization values of these steels were obtained and then the corrosion currents were determined with the aid of cathodic polarization curves. It has been observed that both the amount of martensite and the morphology of the phase constituents have definite effect on the corrosion behavior of DP steel embedded in concrete. As a result of this study, it is found that corrosion rate of dual-phase steel has increased with increase amount of martensite.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Corrosion; Concrete; Microstructure; Martensite; Dual-phase steel